1980
DOI: 10.1038/bjc.1980.172
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition and age at first birth in breast-cancer risk

Abstract: Summary.-Urban/rural breast-cancer incidence ratios in the state of Iowa for 1950 and 1969-71 were contrasted with corresponding urban and rural distributions of age-at-first-birth and population nutrition, variables measured 15 years before each morbidity survey and putatively related to breast-cancer incidence. Over the study interval, the decline in the urban/rural breast-cancer incidence ratio correlated better with changing nutritional patterns than with changing age-at-first-birth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1982
1982
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 9 publications
1
3
0
Order By: Relevance
“…For instance, for Yazd city that was in 90th percentile of incidence rate of breast cancer, with increasing one percent in urbanization, the incidence rate increased 0.13. This result is similar to those of the studies of Doll et al and Nasca et al and (Haenszel et al, 1956;Nasca et al, 1980;Pawlega and Wallace, 1980;Mahoney et al, 1990;Doll, 1991;Robert et al, 2004), in their studies the cancer incidence had an increasing trend with increasing the urbanization. With urbanization the central factor of breast cancer (e.g.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…For instance, for Yazd city that was in 90th percentile of incidence rate of breast cancer, with increasing one percent in urbanization, the incidence rate increased 0.13. This result is similar to those of the studies of Doll et al and Nasca et al and (Haenszel et al, 1956;Nasca et al, 1980;Pawlega and Wallace, 1980;Mahoney et al, 1990;Doll, 1991;Robert et al, 2004), in their studies the cancer incidence had an increasing trend with increasing the urbanization. With urbanization the central factor of breast cancer (e.g.…”
Section: Discussionsupporting
confidence: 91%
“…Only a handful of studies have addressed urban/rural variation in breast cancer incidence and mortality. And also there are studies that reported a statistically significant and excess of breast cancer in urban compared to rural areas (Haenszel et al, 1956;NASCA et al, 1980;Pawlega and Wallace, 1980;Mahoney et al, 1990;Doll, 1991;Howe et al, 1993;Valerianova et al, 1994;Vassallo et al, 1994;Robert et al, 2004).With least square model the relationship between covariates and the mean of the response can be estimated. However, this model cannot be applied to evaluate the effects of covariates on other aspects of the response distribution, such as the quartiles.…”
Section: Introductionmentioning
confidence: 99%
“…Only a handful of studies have addressed urban/rural variation in breast cancer incidence and mortality. In general, these studies suggest a statistically significant but moderate excess of breast cancer in urban compared to rural areas [17,18,27,[29][30][31][32][33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%
“…Decreasing fertility has been found to parallel increasing incidence and mortaIity in the United Kingdom and in the United States (Armstrong, 1976;Blot, 1980). Some studies have found that high consumption of fat, animal protein and sugar 10 to 20 years earlier correlated better than changes in child-bearing with increasing breast cancer rates (Hems, 1980;Pawlega and Wallace, 1980;Jakesz et al, 1986). Other studies, reviewed by Bloch et al (1992), have also implicated dietary factors, in particular a lowered risk accompanying high intakes of fruit and vegetables.…”
Section: Incidence Of Female Breast Cancer In Relation To Prevalence mentioning
confidence: 99%